Development of a traffic decongestion model at Constantine city to improve urban mobility: case of the Zouaghi Slimane crossroad (Algeria) - Boukebbab, Salim; Soulmana, Billal; Kelilba, Mounira (Technology audit and production reserves, 2024)
The object of the study is modeling traffic congestion. For modeling traffic congestion in the aim to get better fluidity of road traffic mainly in urban areas, it is necessary to use powerful computers, ahead the complexity of the task. Because, road traffic is a complex phenomenon especially at crossroads, firstly due to the high number of users who use it, secondly the nature of the crossroads which have a complex mesh network. In this paper, a mathematical approach based on the Greenshield model who interested in the study of traffic performance at crossroads is developed. This model permit to control and regulate traffic urban which must meet various objectives like: minimizing wait times for vehicles at crossroads, optimization of traffic flows on the road network. The application treated in this papier is the Zouaghi Slimane crossroads of Constantine city (Algeria). According obtained results, the time spent at crossroads Zouaghi Slimane can reach more than 45 minutes and more for day. This situation brings to asking the following question: how to reduce the travel time lost at this crossroads? To give the answer at this last question, the first step is to considering the different variables that characterize the progressive movement of vehicles on a road. In the objective to give a mathematical formulation, which links, the number of vehicles present at time t over a length L of the road. Speed is one of the basic parameters of traffic flow, the relationship between the fundamental parameters of traffic considers the different variables that characterize the progressive movement of vehicles on a road permit to give a mathematical formulation which links the number of vehicles present at time “t” over a length “L” of the road. The main objective is to bring out indicators such as speeds, density and critical flows allowing to set up a dynamic management of the traffic, for a decongestion the crossroads Zouaghi Slimane.